Behavioral, histopathological and biochemical impairments observed in mice envenomed by the scorpion: Hottentota gentili (Pallary, 1924). (1st September 2015) - El Hidan, Moulay Abdelmonaim; Touloun, Oulaid; El Hiba, Omar; Chait, Abderrahman; Eddine Hafid, Jamal; Boumezzough, Ali
Abstract: Hottentota gentili is a black scorpion which has been considered as dangerous specie by many authors. However there are no data regarding minimal lethal dose and effects of the scorpion venom till now. We therefore aimed, by the present investigation, to assess on the one hand, the LD50 of H. gentili venom by sublethal injection and the effects on some vital organs, by a histological and a biochemical tools. On the other hand, the possible neurobehavioral impairments, in Swiss mice, 3 h, 6 h and 12 h following envenomation. The LD50 of H. gentili scorpion venom was found to be 0.46 mg/kg by subcutaneous injection route. Venom produced focal fragmentation of myocardial fibers, while lungs showed rupture of the alveolar structure. Intestines showed selective histopathological changes. Concomitantly, there was a significant rise in the serum enzymes levels, as well as hyperkalemia and a high level of plasma albumine and creatine. Proteinuria was also observed. The observed behavioral effects were a hypoactivity in the both experiments 30 min and 3 h after injection. The envenomation produced an increased immobility time only 30 min and 3 h post injection in the tail suspension test (TST). Graphical abstract: Highlights: The LD50 of Hottentota gentili scorpion venom was found to be 0.46 mg/kg by subcutaneous injection route. H. gentili venom produces histopathological changes in organs such as kidney, heart and lungs. H. gentili venom produces a significant rise in the serum enzymes levels of AST, ALT, CPK and LDH. H. gentili venom induces time dependant neuro-behavioral impairments.